Troubleshooting the Excavator-205 Bucket Wheel Substructure Automatic Lubrication System - Marthin Jehuda; Rizqullah Nurfallah; Fajar Ezra Sitorus; Gita Basdame Sembiring; Joy Bram Bremanan Tarigan; Fajar Paundra; Ilhan Manzeis (Journal of Industrial and Mechanical Engineering, 2024)
The inappropriate use of heavy equipment in the field's conditions and situations can result in various losses, including low production, failure to meet scheduled targets, or unnecessary repair costs. Troubleshooting in the lubrication system often occurs due to reduced flow in the distributor and clogged distributor lines. The aim of this research study is to understand the troubleshooting process performed on the automatic lubrication system of the Bucket Wheel Excavator-205 substructure. Although automatic lubrication systems are designed to enhance efficiency and operational reliability, technical issues can sometimes occur, disrupting system performance. Data collection methods include field observations, data analysis, and experiments. The research findings indicate that common problems include lubricant leaks, decreased lubrication pressure, and sensor malfunctions. Based on the analysis of causes, appropriate solutions have been implemented, including mechanical repairs, replacement of damaged components, and enhanced preventive maintenance. It is hoped that the results of this research will contribute to improving the efficiency, reliability, and lifespan of the automatic lubrication system on Bucket Wheel Excavator-205, as well as providing guidance for better maintenance in the future.